HUBUNGAN FAKTOR INDIVIDU DAN FAKTOR LINGKUNGAN TERHADAP GEJALA SICK BUILDING SYNDROME PADA STAF TENAGA KE PENDIDIKAN DI FAKULTAS KEDOKTERAN UPN VETERAN JAKARTA TAHUN 2020 - Ratna Dwi Krismondani; Aulia Chairani; Nunuk Nugrohowati (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2021)
Background: Sick building syndrome (SBS) are collection of symptoms suffered by workers in offices and other buildings with symptoms such as headaches and respiratory problems. Based on report of the National Health Organization there are estimated 2.2 million deaths due indoor pollution. Where 70-80% of individuals spend their time working indoors. Methods and Samples: The study had used a cross sectional method which aims to determine relationship between individual and environmental factors that influence onset symptoms of SBS. The research data were collected through questionnaires. The sample in this study were 49 educational staff at the Faculty of Medicine UPN Veteran Jakarta. The sampling technique used total sampling. This study used univariate, bivariate, and multivariate analysis. Results: Bivariate analysis: age (p = 0.02), length of service (p = 0.00), psychosocial conditions (p = 0.00) and room ventilation conditions (p = 0.00). While multivariate analysis: age (p = 0.05; OR = 3.524; 95% CI 1.019-14.914), years of service (p = 0.02; OR = 4.168; 95% CI 1.768-16.520), room ventilation (p = 0.03; OR = 7.167; 95% CI 2.705-27.912), and psychosocial conditions (p = 0.012; OR = 8.714; 95% CI 3.072-29.098). Conclusion: Based on the bivariate analysis, there are significant relationship between age, years of service, psychosocial conditions and room ventilation of symptoms SBS. Meanwhile, based on multivariate analysis, psychosocial status is the most influential factor of symtoms SBS